Certificação e desenvolvimento de marcas como estratégia de diferenciação de produtos: o caso da cadeia agroindustrial da carne bovina - Ribeiro, Paulo Marcelo Tavares (2008)
The aim of this study was to analyze and compare the competitiveness of differentiation systems that use certification and brands as segmentation strategies in the bovine meat market in Brazil. It was developed a qualitative research in a multi case study including a bibliographic review and exploratory interviews. Five cases were identified and chosen to be analyzed: a case of public certification, two cases of private certification, one of publicprivate certification, and one about brand. The case analysis was conducted using an adapted methodology from agri-food chain studies with a model including competitive parameters from the original proposal as well as new parameters from economy of the transaction cost and propriety rights theories. The model for competitive analysis used thirteen parameters and grouped them in tree blocks: government controlled, firm controlled and quasi controlled parameters. These aspects made possible a better comprehension and knowledge about each case, allowing the competitive analysis among each strategy. Main conclusions are: government parameters had higher negative influence in the competitiveness; lack of institutions and good paper definitions on existent institutions involved in the certifications process are serious problems; the brand case presented better competitiveness parameters.